A method for preparing lithium iron phosphate from sulfuric acid slag

Through magnetic separation and acid leaching treatment, the iron content of sulfuric acid residue is increased, and combined with calcining methods of phosphate, lithium source and carbon source, the problem of low utilization efficiency of cheap iron source in the prior art is solved, achieving high efficiency and low cost Preparation of lithium iron phosphate improves product quality and economic value.

CN116119639BActive Publication Date: 2024-12-31SICHUAN YINHE CHEM +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211489130.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-25
Publication Date
2024-12-31
Estimated Expiration
2042-11-25

AI Technical Summary

Technical Problem

The prior art is difficult to effectively use cheap iron sources to prepare high-quality lithium iron phosphate, resulting in an increase in the price of ferrous sulfate. The traditional method is costly, making it difficult to realize the resource utilization of sulfuric acid slag.

Method used

Through multiple magnetic separation and acid leaching treatment, the iron content of the sulfuric acid slag is increased, combined with a mixed calcination method of phosphate, lithium source and carbon source, high-performance lithium iron phosphate is prepared, and spray drying and high-temperature calcination processes are used to achieve high efficiency of the sulfuric acid slag Conversion.

Benefits of technology

The quality and finished product particle size of lithium iron phosphate are improved, the impurity content is reduced, and the efficient and low-cost conversion of sulfuric acid slag is achieved to high-value lithium iron phosphate is simplified, and the production process is saved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a method for preparing lithium iron phosphate from sulfuric acid slag, comprising the following steps: selecting magnetic substances from sulfuric acid slag through a magnetic separator, leaching part of trace elements from non-magnetic sulfuric acid slag through acid, washing with water, grinding, stirring and mixing the refined sulfuric acid slag with phosphate, carbon source and lithium source under wet conditions, demagnetizing after drying, roasting under inert gas protection under high temperature conditions, reducing trivalent iron to divalent iron with carbon, performing air flow crushing after demagnetization, drying, sieving and packaging to obtain finished lithium iron phosphate. The present invention can convert sulfuric acid slag into high-value and high-performance lithium iron phosphate in an efficient and low-cost manner, thereby achieving maximum economic value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium iron phosphate preparation, and more specifically, the present invention relates to a method for preparing lithium iron phosphate from sulfuric acid slag. Background Art

[0002] Lithium iron phosphate (LiFePO4) is a lithium-ion cathode material with stable structure, high theoretical capacity (170mAh / g), good cycle performance, abundant raw material sources, good safety performance and environmental friendliness. It is the cathode material with the greatest potential for large-scale application in the field of energy storage and power batteries in the future. With the development of lithium iron phosphate, the quality of the iron source is the factor that has the greatest impact on the quality of lithium iron phosphate, which has led to the use of cheap iron sources. The iron salt used to prepare lithium iron phosphate cathode materials is generally ferrous sulfate, and the expansion of lithium iron phosphate production capacity has led to a surge in the price of ferrous sulfate crystals, so the selection of emerging cheap iron sources is also urgent.

[0003] Sulfuric acid slag is also called pyrite baking slag or burning slag. It is a kind of chemical waste residue, which is discharged from the process of making sulfuric acid or sulfurous acid from pyrite. Sulfuric acid slag can be used as cement raw material, brick making material, etc. In order to make good use of it and realize the economic value of sulphuric acid slag, an efficient and low-cost method is adopted to convert sulphuric acid slag into high-value and high-performance lithium iron phosphate to achieve the maximum economic value. Summary of the invention

[0004] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.

[0005] In order to achieve these purposes and other advantages according to the present invention, a method for preparing lithium iron phosphate from sulfuric acid slag is provided, comprising the following steps:

[0006] Step 1: transport the sulfuric acid slag to a magnetic separator through a conveyor belt, and the magnetic separator separates non-magnetic substances in the sulfuric acid slag by magnetizing and demagnetizing; acid leaching the sulfuric acid slag after magnetic separation, soaking, separating and washing in acid to obtain refined sulfuric acid slag;

[0007] Step 2: Mix the refined sulfuric acid slag in step 1 with phosphate, carbon source, lithium source and water in proportion, perform a ball milling for pre-dispersion, and then perform a secondary sand milling to obtain a mixed slurry, and perform magnetic separation on the obtained mixed slurry to obtain a precursor slurry;

[0008] Step 3, spray drying the precursor slurry in step 2 to obtain a precursor, and magnetically separating the obtained precursor to obtain a precursor powder;

[0009] Step 4: Place the precursor powder in a high-temperature device, under the protection of an inert gas, heat it up for calcination, cool it down, demagnetize it, crush it, dry it, and sieve it to obtain the finished lithium iron phosphate.

[0010] Preferably, in the step 1, the particle size of the sulphuric acid slag is 50-400 mesh; the magnetic separator is a dry magnetic separator, a wet magnetic separator, or one or more of the above; the magnetic field strength of the magnetic separator is 4000-12000GS; and the number of magnetic separations of the sulphuric acid slag is 1-5 times.

[0011] Preferably, in the step 1, the magnetic separation scheme of the slag includes the following steps:

[0012] S1. Modulate the magnetic field strength of the magnetic separator to 2000-4000GS, place the sulfuric acid slag in the magnetic separator, the magnetically separated material is the high iron material, and the remaining material is the sulfuric acid slag material;

[0013] S2. Modulate the magnetic field strength of the magnetic separator to 6000-8000GS, place the sulfuric acid slag material in the magnetic separator, the material separated by magnetic separation is the sulfuric acid slag to be acid leached, and the remaining material is the tailings.

[0014] Preferably, in the step 1, the solid-liquid ratio of the refined sulfuric acid slag to the acid is 1:3; the acid is one or a combination of hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, etc.; the acid leaching process is to first react at 25-60°C for 1-3h to remove silicon, and then heat to 80-150°C for 1-4h to remove impurities such as aluminum and magnesium.

[0015] Preferably, in step 2, the phosphate is one or more combinations of sodium phosphate, phosphoric acid, ammonium hydrogen phosphate or diammonium phosphate; the carbon source is one or more combinations of glucose, citric acid or sucrose; and the lithium source is one or more combinations of lithium hydroxide, lithium carbonate, lithium dihydrogen phosphate, dilithium hydrogen phosphate, lithium oxalate and lithium nitrate.

[0016] Preferably, in the step 2, the molar ratio of the iron element in the refined sulfuric acid slag to the phosphate in the phosphorus source, the lithium element in the lithium source, and the carbon element in the carbon source is 1: (0.98-1.02): (0.97-1.12): (1.98-2.02).

[0017] Preferably, in the step 2, the solid content of the slurry of sulfuric acid slag, phosphorus source, lithium source, carbon source and water is 30-40%; the particle size of the solid in the secondary sand milling mixed slurry is controlled at D50 of 300-500nm; the magnetic field strength of the magnetic separation is 8000-12000GS, the material separated by the magnetic separation is the precursor slurry, and the remaining material is the tailings.

[0018] Preferably, in the step three, the drying is spray drying, the inlet temperature is 180-220°C, the outlet temperature is 95-105°C, and the spray drying should control the moisture content of the precursor to ≤2%; the magnetic field strength of the magnetic separation is 8000-12000GS, the material separated by the magnetic separation is the tail material E, and the remaining material is the precursor powder.

[0019] Preferably, in step 4, the inert gas is N2, Ar or N2 / Ar mixed gas; the calcination temperature is a two-stage calcination, the heating rate of the first stage calcination temperature is 8-10℃ / min, heating to 200-400℃ for 0.5h, and keeping warm for 1-4h, the heating rate of the second stage calcination program is 8-10℃ / min, heating to 700-800℃ for 0.5h, and keeping warm for 8-10h; the magnetic field strength of the magnetic separation is 8000-12000GS, the material separated by the magnetic separation is the finished lithium iron phosphate product, and the remaining material is the tailings.

[0020] Preferably, in the step 4, the particle size of the lithium iron phosphate product obtained is D50=1.0-3.0 μm, and D99≤15 μm.

[0021] The method for preparing lithium iron phosphate from sulfuric acid slag proposed by the present invention has at least the following beneficial effects:

[0022] (1) The present invention improves the quality of sulfuric acid slag by multiple magnetic separations to obtain sulfuric acid slag with a higher iron content, thereby making the quality of lithium iron phosphate higher and the impurity content less.

[0023] (2) The present invention can process sulfuric acid slag in an efficient and low-cost manner, and convert the sulfuric acid slag into high-value and high-performance lithium iron phosphate, thereby realizing its maximum economic value.

[0024] (3) The present invention obtains refined sulfuric acid slag by magnetic separation, and obtains high-performance lithium iron phosphate by directly mixing the sulfuric acid slag with a phosphorus source, a lithium source, and a carbon source for calcination. This preparation method is simple, cost-saving, and easy to implement in a production line.

[0025] Other features and advantages of the present disclosure will be set forth in the following description, or some features and advantages may be inferred or unambiguously determined from the description, or may be learned by implementing the above-mentioned technology of the present disclosure. DETAILED DESCRIPTION

[0026] The specific scheme proposed by the present invention is described in more detail with reference to several specific embodiments below.

[0027] Example 1

[0028] (1) The sulphuric acid slag (iron grade 83.39%, aluminum, silicon, magnesium, zinc, copper, sulfur, potassium, sodium contents 1.4%, 2.68%, 3.36%, 0.9106%, 0.2798%, 1.6%, 0.015%, 0.0333% respectively) passing through a 200 mesh sieve is transported to a magnetic separator via a conveyor belt. The magnetic separator modulates the magnetic force to 4000 GS. The material magnetically separated is high iron material, and the remaining material is sulphuric acid slag material; the sulphuric acid slag material is placed in a magnetic separator. The magnetic separator modulates the magnetic force to 8000 GS. The material magnetically separated is sulphuric acid slag to be acid-leached, and the remaining material is tailings A; the above steps are repeated three times to effectively separate the magnetic substances in the sulphuric acid slag.

[0029] (2) Soaking the sulfuric acid slag to be acid-leached after magnetic separation in sulfuric acid with a concentration of 6 mol / L and a solid-liquid ratio of the sulfuric acid slag to sulfuric acid of 1:3. The acid-leaching process is to first react at 25-60°C for 2 hours to remove silicon, then heat to 80-150°C for 2 hours to remove impurities such as aluminum and magnesium, separate and wash with water to obtain refined sulfuric acid slag.

[0030] (3) According to the molar ratio of iron, phosphate, lithium and carbon being 1:1:1:2, weigh refined sulfuric acid slag (mainly ferric oxide, purity 80%), sodium phosphate (Na3PO4, purity 99.9%), lithium carbonate (Li2CO3, purity 99.9%), glucose (C6H 12 O6, food grade), mix the ingredients, add water to make the solid content in the slurry be 35%, ball mill the mixture under wet conditions, preliminarily disperse the mixture by ball milling, sand mill the mixture after ball milling, control the sand milling particle size at D50 of 300-400nm, and obtain a mixed slurry with higher fineness, place the mixed slurry in a magnetic separator, modulate the magnetic force of 12000GS for magnetic separation and demagnetization, the material separated by magnetic separation is the precursor slurry, and the remaining material is the tail material B.

[0031] (4) The precursor slurry is spray dried to obtain precursor powder. The spray drying pressure is 4 MPa, the spray drying inlet temperature is 190 °C, the outlet temperature is 95 °C, the spray drying granulation particle size D50 should be controlled at 5-8 μm, and the water content is controlled at ≤2%. The precursor powder is placed in a magnetic separator and the magnetic field strength is modulated to 12000 GS for magnetic separation. The precursor material is demagnetized. The magnetically separated material is the tail material C, and the remaining material is the precursor powder.

[0032] (5) The precursor powder is placed in a high-temperature device for calcination, and an inert gas N2 is introduced to protect it. The temperature is raised to 250°C in 0.5h, and kept at this temperature for 1h. The temperature is then raised to 750°C after 1h, and kept at this temperature for 10h. The trivalent iron is reduced to divalent iron by carbon. After the calcination is completed, the temperature is cooled to less than 50°C and taken out. The magnetic separation is carried out at a magnetic force of 12000GS in a magnetic separator. The magnetically separated material is the finished lithium iron phosphate product, and the remaining material is the tail material D. The material is then crushed by a jet mill, dried, sieved, and packaged to obtain the lithium iron phosphate material of Example 1.

[0033] The first embodiment was tested, and the obtained lithium iron phosphate finished product had a particle size of D50 = 2.54 μm, D99 ≤ 15 μm, an iron content of 33.49%, a phosphorus content of 19.27%, a lithium content of 4.36%, an impurity content of 0.17%, a carbon content of 4.36%, and a moisture content of <0.1%.

[0034] Example 2

[0035] (1) The sulphuric acid slag (iron grade 83.39%, aluminium, silicon, magnesium, zinc, copper, sulfur, potassium and sodium contents of 1.4%, 2.68%, 3.36%, 0.9106%, 0.2798%, 1.6%, 0.015% and 0.0333% respectively) passing through a 400-mesh sieve is transported to a magnetic separator via a conveyor belt. The magnetic force of the magnetic separator is modulated to 3000 GS. The material magnetically separated is high iron material, and the remaining material is sulphuric acid slag material; the sulphuric acid slag material is placed in a magnetic separator. The magnetic force of the magnetic separator is modulated to 6000 GS. The material magnetically separated is sulphuric acid slag to be acid-leached, and the remaining material is tailings A; the above steps are repeated 4 times to effectively separate the magnetic substances in the sulphuric acid slag.

[0036] (2) Soaking the sulfuric acid slag to be acid-leached after magnetic separation in nitric acid, wherein the concentration of the nitric acid is 6 mol / L, and the solid-liquid ratio of the sulfuric acid slag to the nitric acid is 1:3, wherein the acid leaching process is to first react at 25-60°C for 3 hours to remove silicon, then heat to 80-150°C for 1 hour to remove impurities such as aluminum and magnesium, separate and wash with water to obtain refined sulfuric acid slag.

[0037] (3) According to the molar ratio of iron, phosphate, lithium and carbon being 1:0.98:1.12:2.02, weigh refined sulfuric acid slag (mainly ferric oxide, purity 80%), diammonium phosphate (NH4H2PO4, purity 99.9%), lithium carbonate (Li2CO3, purity 99.9%), glucose (C6H 12O6, food grade), mix the ingredients, add water to make the solid content in the slurry be 40%, ball mill the mixture under wet conditions, preliminarily disperse the mixture by ball milling, sand mill the mixture after ball milling, control the sand milling particle size at D50 of 300-400nm, and obtain a mixed slurry with higher fineness, place the mixed slurry in a magnetic separator, modulate the magnetic force of 10000GS for magnetic separation and demagnetization, the material separated by magnetic separation is the precursor slurry, and the remaining material is the tail material B.

[0038] (4) The precursor slurry is spray dried to obtain precursor powder. The spray drying pressure is 4 MPa, the spray drying inlet temperature is 180 °C, the outlet temperature is 100 °C, the spray drying granulation particle size D50 should be controlled at 5-8 μm, and the water content is controlled at ≤1%. The precursor powder is placed in a magnetic separator and the magnetic force is modulated to 10000 GS for magnetic separation. The precursor material is demagnetized. The magnetically separated material is the tail material C, and the remaining material is the precursor powder.

[0039] (5) The precursor powder is placed in a high-temperature device for calcination, and an inert gas Ar is introduced to protect it. The temperature is raised to 200°C in 0.5 h, and kept at this temperature for 4 h. The temperature is then raised to 700°C after 1 h, and kept at this temperature for 10 h. The trivalent iron is reduced to divalent iron by carbon. After the calcination is completed, the temperature is cooled to less than 50°C and taken out. The magnetic separation is performed at a magnetic force of 10000 GS in a magnetic separator. The magnetically separated material is the finished lithium iron phosphate product, and the remaining material is the tail material D. The material is then crushed by a jet mill, dried, sieved, and packaged to obtain the lithium iron phosphate material of Example 1.

[0040] The first embodiment was tested, and the obtained lithium iron phosphate finished product had a particle size of D50 = 1.78 μm, D99 ≤ 15 μm, an iron content of 34.79%, a phosphorus content of 20.72%, a lithium content of 4.52%, an impurity content of 0.14%, a carbon content of 4.82%, and a moisture content of <0.1%.

[0041] Example 3

[0042] (1) The sulphuric acid slag (iron grade 83.39%, aluminium, silicon, magnesium, zinc, copper, sulfur, potassium and sodium contents of 1.4%, 2.68%, 3.36%, 0.9106%, 0.2798%, 1.6%, 0.015% and 0.0333% respectively) passing through a 50-mesh sieve is transported to a magnetic separator via a conveyor belt. The magnetic force of the magnetic separator is modulated to 2000 GS. The material magnetically separated is high iron material, and the remaining material is sulphuric acid slag material; the sulphuric acid slag material is placed in a magnetic separator. The magnetic force of the magnetic separator is modulated to 7000 GS. The material magnetically separated is sulphuric acid slag to be acid-leached, and the remaining material is tailings A; the above steps are repeated three times to effectively separate the magnetic substances in the sulphuric acid slag.

[0043] (2) Soaking the sulfuric acid slag to be acid-leached after magnetic separation in phosphoric acid, wherein the concentration of the phosphoric acid is 6 mol / L, and the solid-liquid ratio of the sulfuric acid slag to the phosphoric acid is 1:3. The acid leaching process is to first react at 25-60°C for 1 hour to remove silicon, then heat to 80-150°C for 4 hours to remove impurities such as aluminum and magnesium, separate and wash with water to obtain refined sulfuric acid slag with a purity of about 80% of ferric oxide.

[0044] (3) According to the molar ratio of iron, phosphate, lithium and carbon being 1:1.02:0.97:1.98, weigh refined sulfuric acid slag (mainly ferric oxide, purity 80%), sodium phosphate (Na3PO4, purity 99.9%), lithium nitrate (LiNO 3, Purity 99.9%), glucose (C6H 12 O6, food grade), mix the ingredients, add water to make the solid content in the slurry be 40%, ball mill the mixture under wet conditions, preliminarily disperse the mixture by ball milling, sand mill the mixture after ball milling, control the sand milling particle size at D50 of 300-400nm, and obtain a mixed slurry with higher fineness, place the mixed slurry in a magnetic separator, modulate the magnetic force of 8000GS for magnetic separation and demagnetization, the material separated by magnetic separation is the precursor slurry, and the remaining material is the tail material B.

[0045] (4) The precursor slurry is spray dried to obtain precursor powder. The spray drying pressure is 4 MPa, the spray drying inlet temperature is 180 °C, the outlet temperature is 100 °C, the spray drying granulation particle size D50 should be controlled at 5-8 μm, and the water content is controlled at ≤2%. The precursor powder is placed in a magnetic separator and the magnetic force is modulated to 8000 GS for magnetic separation. The precursor material is demagnetized. The magnetically separated material is the tail material C, and the remaining material is the precursor powder.

[0046] (5) The precursor powder is placed in a high-temperature device for calcination, and a mixed gas of inert gas N2 and Ar is introduced to protect it. The temperature is raised to 200°C in 0.5h and kept warm for 4h. The temperature is then raised to 700°C after 1h and kept warm for 10h. The trivalent iron is reduced to divalent iron by carbon. After calcination is completed, the temperature is cooled to less than 50°C and taken out. The magnetic separation is carried out at a magnetic force of 8000GS in a magnetic separator. The magnetically separated material is the finished lithium iron phosphate product, and the remaining material is the tail material D. The material is then crushed by a jet mill, dried, sieved, and packaged to obtain the lithium iron phosphate material of Example 1.

[0047] The first embodiment was tested, and the obtained lithium iron phosphate finished product had a particle size of D50=1.67μm, D99≤15μm, an iron content of 32.64%, a phosphorus content of 18.65%, a lithium content of 4.38%, an impurity content of 0.19%, a carbon content of 4.23%, and a moisture content of <0.1%.

[0048] Finally, it should be noted that the above-described embodiments are only specific implementations of the present invention, which are used to illustrate the technical solutions of the present invention, rather than to limit them. The protection scope of the present invention is not limited thereto. Although the present invention is described in detail with reference to the above-described embodiments, ordinary technicians in the field should understand that any technician familiar with the technical field can still modify the technical solutions recorded in the above-described embodiments within the technical scope disclosed by the present invention, or can easily think of changes, or make equivalent replacements for some of the technical features therein; and these modifications, changes or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be the protection scope of the claims.

Claims

1. A method for preparing lithium iron phosphate from sulfuric acid slag, characterized in that: The following steps are involved: Step 1: transport the sulfuric acid slag to a magnetic separator through a conveyor belt, and separate the magnetic substances in the sulfuric acid slag by magnetizing and demagnetizing; acid leaching the non-magnetic sulfuric acid slag after magnetic separation, and soaking, separating and washing in acid to obtain refined sulfuric acid slag; Step 2: Mix the refined sulfuric acid slag in step 1 with phosphate, carbon source, lithium source and water in proportion, perform a ball milling for pre-dispersion, and then perform a secondary sand milling to obtain a mixed slurry, and perform magnetic separation on the obtained mixed slurry to obtain a precursor slurry; Step 3, spray drying the precursor slurry in step 2 to obtain a precursor, and magnetically separating the obtained precursor to obtain a precursor powder; Step 4: placing the precursor powder in a high-temperature device, under the protection of an inert gas, heating up for calcination, cooling down, demagnetizing, crushing, drying, and sieving to obtain a finished product of lithium iron phosphate; In the step 1, the magnetic separation scheme of the sulphuric acid slag includes the following steps: S1. Modulate the magnetic field strength of the magnetic separator to 2000-4000GS, place the sulphuric acid slag in the magnetic separator, the magnetically separated material is the high iron material, and the remaining material is the sulphuric acid slag material; S2, the magnetic field strength of the magnetic separator is adjusted to 6000-8000GS, and the sulfuric acid slag material is placed in the magnetic separator. The material separated by magnetic separation is the sulfuric acid slag to be acid leached, and the remaining material is the tailings A; In the step 1, the solid-liquid ratio of sulfuric acid slag to acid is 1:3; the acid is one or more of hydrochloric acid, sulfuric acid, nitric acid and phosphoric acid; the acid leaching process is to first react at 25-60° C. for 1-3 hours to remove silicon, and then heat to 80-150° C. for 1-4 hours to remove aluminum and magnesium impurities; In the step 2, the magnetic field strength of the magnetic separation is 8000-12000GS, the material separated by the magnetic separation is the precursor slurry, and the remaining material is the tail material B; In the step 3, the magnetic field strength of the magnetic separation is 8000-12000GS, the material separated by the magnetic separation is the tail material C, and the remaining material is the precursor powder; In the step 4, the magnetic field strength is 8000-12000GS, the magnetically separated material is the finished lithium iron phosphate product, and the remaining material is the tail material D.

2. The method for preparing lithium iron phosphate from sulfuric acid slag according to claim 1, characterized in that: In the step 1, the particle size of the sulphuric acid slag is 50-400 mesh; the magnetic separator is a dry magnetic separator, a wet magnetic separator or one or more of the above; the magnetic field strength of the magnetic separator is 4000-12000GS; the number of magnetic separations of the sulphuric acid slag is 1-5 times.

3. The method for preparing lithium iron phosphate from sulfuric acid slag according to claim 1, characterized in that: In step 2, the phosphate is one or more combinations of sodium phosphate, ammonium dihydrogen phosphate or phosphoric acid; the carbon source is one or more combinations of glucose, citric acid or sucrose; the lithium source is one or more combinations of lithium hydroxide, lithium carbonate, lithium dihydrogen phosphate, dilithium hydrogen phosphate, lithium oxalate, and lithium nitrate.

4. The method for preparing lithium iron phosphate from sulfuric acid slag according to claim 1, characterized in that: In the step 2, the molar ratio of the iron element in the refined sulfuric acid slag to the phosphate in the phosphorus source, the lithium element in the lithium source, and the carbon element in the carbon source is 1: (0.98-1.02): (0.97-1.12): (1.98-2.02).

5. The method for preparing lithium iron phosphate from sulfuric acid slag according to claim 1, characterized in that: In the step 2, the solid content of the mixed slurry of the sulfuric acid slag, phosphorus source, lithium source, carbon source and water is 30-40%; the particle size of the solid in the secondary sand-milled mixed slurry is controlled at D90 of 300-500nm.

6. The method for preparing lithium iron phosphate from sulfuric acid slag according to claim 1, characterized in that: In the step 3, the drying is spray drying, the inlet temperature is 180-220° C., the outlet temperature is 95-105° C., and the spray drying should control the water content of the precursor to ≤2%.

7. The method for preparing lithium iron phosphate from sulfuric acid slag according to claim 1, characterized in that: In the step 4, the inert gas is N2, Ar or N2 / Ar mixed gas; the calcination temperature is a two-stage calcination, the heating rate of the first stage calcination temperature is 8-10℃ / min, the temperature is raised to 200-400℃ for 0.5h, and the temperature is kept for 1-4h; the heating rate of the second stage calcination program is 8-10℃ / min, the temperature is raised to 700-800℃ for 0.5h, and the temperature is kept for 8-10h.

8. The method for preparing lithium iron phosphate from sulfuric acid slag according to claim 1, characterized in that: In the step 4, the particle size of the lithium iron phosphate product obtained is D90=1.0-3.0μm, D99≤15μm.